Dietary effects of hydroponic wheat sprouted fodder on growth performance of turkey (Research in Agriculture Livestock and Fisheries, 2019)
The study was conducted at Faculty of Veterinary and Animal Science, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur, Bangladesh to determine the nutritional composition and economic value of hydroponic wheat sprouted fodder (HWSF) replaced by commercial concentrate feed (CCF) and it’s effect on growth performance of turkey. A total of 75 poults were selected and randomly assigned into five groups (T1, T2, T3, T4 and T5), each group with 3 replications having 15 birds in each. T1 considered as control group and fed only CCF, where T2, T3, T4 and T5 groups fed 95, 90, 85 and 80% CCF along with 5, 10, 15 and 20% HWSF, respectively. The amount of DM, CP and NFE were significantly higher (P